Low-cost preparation method of artificial graphite negative electrode of high-energy-density energy storage battery
By mixing coal-based needle coke and pitch needle coke, and combining microwave-assisted roasting and magnetic field-assisted graphitization technologies, the particle morphology and crystal structure are optimized, solving the problems of high cost, high energy consumption and backward environmental protection in the traditional preparation of artificial graphite anodes, and realizing the low-cost preparation of high-energy-density energy storage battery anodes.
Patent Information
- Application Number
- CN202511041057.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2025-11-04
AI Technical Summary
Traditional artificial graphite anodes are expensive to produce, have complex processes, and consume a lot of energy. They also suffer from uneven temperature, low energy efficiency, and outdated environmental protection practices, which limit the widespread application of energy storage batteries.
By using a mixture of coal-based needle coke and pitch needle coke, combined with microwave-assisted roasting and magnetic field-assisted graphitization technologies, and through intelligent temperature control and efficient equipment, the particle morphology and crystal structure are optimized. Combined with precise parameter control and environmentally friendly treatment, production costs are reduced.
This has enabled the low-cost preparation of high-energy-density battery anode materials, improved the overall performance of the materials, ensured product quality stability and production continuity, and reduced the costs of raw materials, energy and equipment.
Smart Images

Figure CN120887418A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery manufacturing technology, specifically to a low-cost method for preparing artificial graphite anodes for high-energy-density energy storage batteries. Background Technology
[0002] With the booming development of new energy vehicles and portable electronic devices, the market demand for energy storage batteries continues to rise, and the requirements for battery energy density, cost and cycle life are becoming increasingly stringent. Artificial graphite anode materials have become the mainstream choice for lithium-ion battery anode materials due to their high specific capacity, excellent cycle stability and safety. However, the traditional artificial graphite anode preparation process has problems such as high raw material cost, complex process and high energy consumption, resulting in high production costs, which seriously restricts the widespread application of energy storage batteries in large-scale energy storage and electric vehicle fields.
[0003] Currently, most common methods for preparing artificial graphite anodes use a single raw material, making it difficult to fully utilize the complementary advantages of different raw materials and limiting the improvement of anode material energy density. In terms of production processes, traditional crushing and grinding equipment is inefficient and energy-intensive, and the shaping and granulation stages lack precise control, resulting in poor product quality stability. In the calcination and graphitization stages, conventional heating methods suffer from uneven temperature and low energy utilization, affecting the physicochemical properties of the material. In addition, the desulfurization, dust removal, and waste gas treatment technologies are outdated, which not only increases treatment costs but also poses the risk of exceeding pollutant emission standards. To address these issues, we propose a low-cost preparation method for artificial graphite anodes for high-energy-density energy storage batteries. Summary of the Invention
[0004] To address the aforementioned technical problems, a low-cost method for preparing artificial graphite anodes for high-energy-density energy storage batteries is provided. This technical solution solves the problems mentioned above.
[0005] To achieve the above objectives, the technical solution adopted in this invention is: a low-cost preparation method for artificial graphite anodes of high-energy-density energy storage batteries, the preparation steps of which are as follows:
[0006] S1. Prepare raw coke materials, including coal-based needle coke and pitch needle coke. Use a crusher to initially crush large pieces of raw coke to reduce particle size. Mix and blend the coal-based needle coke and pitch needle coke.
[0007] S2. The mixed raw coke is dried by heat conduction to remove moisture. The raw coke is then ground into powder using a grinding mill. The shape of the particles is optimized and adjusted using a shaping device to improve the sphericity of the particles. Granulation is then performed using a horizontal reactor.
[0008] S3. Calcination: The processed raw coke is fed into the calcination equipment. Based on microwave-assisted calcination, the physical and chemical properties are changed, and the temperature distribution is intelligently controlled during the calcination process.
[0009] S4. Graphitization, based on magnetic field-assisted technology, involves applying a magnetic field at high temperature to transform the crystal structure of the material. Dust and impurities adhering to the surface of the material are removed by cooling and dust removal equipment, and sulfur is removed from the material by desulfurization equipment. The waste gas is then treated and discharged.
[0010] S5. Finished product processing: The graphitized material is batch-mixed to ensure uniform mixing of different batches. Magnetic separation equipment is used to remove magnetic impurities from the material. The demagnetized material is then packaged and stored.
[0011] Preferably, in step S1, the ratio of coal-based needle coke to pitch needle coke is 10:0, 7:3, 5:5, 3:7, and 0:10. In the coke crushing stage, a dual-rotor impact crusher is used for two-stage crushing. After being impacted and crushed on the high-speed rotating first-stage rotor, the coke is thrown against the impact plate for further collision and crushing. After fine crushing by the second-stage rotor, the particle size is reduced.
[0012] Preferably, in step S2, a vacuum rake dryer is used for drying, with the vacuum level controlled between -0.08MPa and -0.095MPa during operation; the heating temperature of the jacket and hollow shaft is 120-150℃, and heat is transferred through heat conduction; the speed of the rake agitator is 10-15r / min, the drying time is 2-4h, and drying is stopped when the moisture content of the material drops to 0.5%-1%.
[0013] Preferably, in step S2, the feed rate of the grinding mill is 80-120 kg / h, the compressed air pressure is 0.6-0.8 MPa, and the airflow rate is 30-50 m³ / h. 3 The speed is increased to provide sufficient kinetic energy for the material to collide and crush within the grinding chamber, resulting in a finished powder particle size of 10-50μm.
[0014] Preferably, in step S2, granulation is carried out in a horizontal reactor with a rotation speed of 5-10 r / min, a spray pressure of 0.3-0.5 MPa from the atomizing nozzle, an inlet hot air temperature of 200-250℃ and an outlet temperature of 80-110℃ for drying and granulation, and a sieving structure is provided to separate unqualified particles for regranulation.
[0015] Preferably, the intelligent temperature distribution control step in step S3 is as follows:
[0016] Multiple temperature sensors are installed inside the roasting equipment to obtain the surface temperature of the raw coke; temperature data is acquired every 10-20 seconds.
[0017] The collected data is uploaded to the control system in real time via Ethernet. Based on machine learning algorithms, historical and current data are analyzed to establish a temperature distribution model, predict the temperature change trend under different microwave powers and roasting times, identify local temperature anomalies caused by differences in density and moisture content of raw coke, and generate temperature deviation warnings.
[0018] Based on the temperature distribution model and preset process parameters, the required microwave power adjustment value for each region is calculated. When the local temperature is detected to be too high, the power of the corresponding microwave generator in that region is automatically reduced; when the temperature in a region is insufficient, the microwave output is increased.
[0019] Preferably, in step S4, magnetic field-assisted technology is introduced in the graphitization process. A superconducting magnet system is set up around the high-temperature equipment to create a strong magnetic field environment. The superconducting magnet is made of niobium-titanium superconducting material. After the material enters the graphitization furnace, the magnetic field parameters are adjusted to rotate at a speed of 0.5-2 r / s, and the magnetic field strength is dynamically adjusted within the range of 3-10T.
[0020] Preferably, the superconducting magnet system is equipped with a monitoring device that uses an X-ray diffractometer to detect changes in the crystal structure of the material online. A crystal structure analysis spectrum is generated every 10-15 minutes. The detection data is compared with a preset crystal structure model, and the magnetic field strength, direction, and high-temperature process parameters are adjusted when differences are found.
[0021] Preferably, the step in step S4 where the desulfurization unit removes sulfur from the material is as follows:
[0022] Physical adsorption pretreatment is adopted. In a packed fixed-bed adsorption tower, modified activated carbon adsorbent is used to capture free sulfur and small molecule sulfur-containing compounds. The adsorbent is regenerated by hot nitrogen purging.
[0023] The sulfur compounds are converted into hydrogen sulfide for deep desulfurization in the biological desulfurization reactor.
[0024] During waste gas treatment, the gas passes through an alkaline scrubbing absorption tower where it reacts with acidic sulfur-containing gases, and the alkaline solution is regenerated and recycled. Then, it enters a biological filter where microorganisms degrade organic sulfur.
[0025] After deep purification by activated carbon adsorption tower, the waste is discharged at high altitude after meeting the standards.
[0026] Preferably, in step S5, different batches of materials are mixed evenly using a planetary mixer.
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0028] This invention combines raw material mixing and doping with advanced processes to optimize particle morphology and crystal structure, improve the overall performance of materials, meet high-end demands, and shorten processing time at each stage by working in synergy with an efficient equipment and intelligent monitoring and control system. This reduces rework, ensures continuous production, and reduces raw material, energy, and equipment costs by precise parameter control and equipment maintenance design. The intelligent monitoring and closed-loop control system runs through the entire process, strictly controlling production parameters to ensure stable product quality, reduce batch differences, and keep production costs low. Attached Figure Description
[0029] Figure 1 This is a flowchart of the preparation steps of the present invention. Detailed Implementation
[0030] The following description is intended to disclose the invention and enable those skilled in the art to implement it. The preferred embodiments described below are merely examples, and other obvious variations will occur to those skilled in the art.
[0031] Example 1
[0032] A low-cost method for preparing artificial graphite anodes for high-energy-density energy storage batteries, comprising the following steps:
[0033] S1. Prepare raw coke material, specifically coal-based needle coke; pass the raw coke through a crusher to initially crush large pieces of raw coke and reduce particle size;
[0034] S2. Dry the raw coke by removing moisture through heat conduction, grind the raw coke into powder using a grinding mill, optimize and adjust the shape of the particles using a shaping device to improve the sphericity of the particles, and granulate using a horizontal reactor.
[0035] S3. Calcination: The processed raw coke is fed into the calcination equipment. Based on microwave-assisted calcination, the physical and chemical properties are changed, and the temperature distribution is intelligently controlled during the calcination process.
[0036] S4. Graphitization, based on magnetic field-assisted technology, involves applying a magnetic field at high temperature to transform the crystal structure of the material. Dust and impurities adhering to the surface of the material are removed by cooling and dust removal equipment, and sulfur is removed from the material by desulfurization equipment. The waste gas is then treated and discharged.
[0037] S5. Finished product processing: The graphitized material is batch-mixed to ensure uniform mixing of different batches. Magnetic separation equipment is used to remove magnetic impurities from the material. The demagnetized material is then packaged and stored.
[0038] Example 2
[0039] A low-cost method for preparing artificial graphite anodes for high-energy-density energy storage batteries, comprising the following steps:
[0040] S1. Prepare raw coke materials, including coal-based needle coke and pitch needle coke, with a ratio of 7:3. Pass the raw coke through a crusher to initially crush large pieces of raw coke and reduce particle size. Mix and blend the coal-based needle coke and pitch needle coke.
[0041] S2. The mixed raw coke is dried by heat conduction to remove moisture. The raw coke is then ground into powder using a grinding mill. The shape of the particles is optimized and adjusted using a shaping device to improve the sphericity of the particles. Granulation is then performed using a horizontal reactor.
[0042] S3. Calcination: The processed raw coke is fed into the calcination equipment. Based on microwave-assisted calcination, the physical and chemical properties are changed, and the temperature distribution is intelligently controlled during the calcination process.
[0043] S4. Graphitization, based on magnetic field-assisted technology, involves applying a magnetic field at high temperature to transform the crystal structure of the material. Dust and impurities adhering to the surface of the material are removed by cooling and dust removal equipment, and sulfur is removed from the material by desulfurization equipment. The waste gas is then treated and discharged.
[0044] S5. Finished product processing: The graphitized material is batch-mixed to ensure uniform mixing of different batches. Magnetic separation equipment is used to remove magnetic impurities from the material. The demagnetized material is then packaged and stored.
[0045] Example 3
[0046] A low-cost method for preparing artificial graphite anodes for high-energy-density energy storage batteries, comprising the following steps:
[0047] S1. Prepare raw coke materials, including coal-based needle coke and pitch needle coke, with a ratio of 5:5. Pass the raw coke through a crusher to initially crush large pieces of raw coke and reduce particle size. Mix and blend the coal-based needle coke and pitch needle coke.
[0048] S2. The mixed raw coke is dried by heat conduction to remove moisture. The raw coke is then ground into powder using a grinding mill. The shape of the particles is optimized and adjusted using a shaping device to improve the sphericity of the particles. Granulation is then performed using a horizontal reactor.
[0049] S3. Calcination: The processed raw coke is fed into the calcination equipment. Based on microwave-assisted calcination, the physical and chemical properties are changed, and the temperature distribution is intelligently controlled during the calcination process.
[0050] S4. Graphitization, based on magnetic field-assisted technology, involves applying a magnetic field at high temperature to transform the crystal structure of the material. Dust and impurities adhering to the surface of the material are removed by cooling and dust removal equipment, and sulfur is removed from the material by desulfurization equipment. The waste gas is then treated and discharged.
[0051] S5. Finished product processing: The graphitized material is batch-mixed to ensure uniform mixing of different batches. Magnetic separation equipment is used to remove magnetic impurities from the material. The demagnetized material is then packaged and stored.
[0052] Example 4
[0053] A low-cost method for preparing artificial graphite anodes for high-energy-density energy storage batteries, comprising the following steps:
[0054] S1. Prepare raw coke materials, including coal-based needle coke and pitch needle coke, with a ratio of 3:7. Pass the raw coke through a crusher to initially crush large pieces of raw coke and reduce particle size. Mix and blend the coal-based needle coke and pitch needle coke.
[0055] S2. The mixed raw coke is dried by heat conduction to remove moisture. The raw coke is then ground into powder using a grinding mill. The shape of the particles is optimized and adjusted using a shaping device to improve the sphericity of the particles. Granulation is then performed using a horizontal reactor.
[0056] S3. Calcination: The processed raw coke is fed into the calcination equipment. Based on microwave-assisted calcination, the physical and chemical properties are changed, and the temperature distribution is intelligently controlled during the calcination process.
[0057] S4. Graphitization, based on magnetic field-assisted technology, involves applying a magnetic field at high temperature to transform the crystal structure of the material. Dust and impurities adhering to the surface of the material are removed by cooling and dust removal equipment, and sulfur is removed from the material by desulfurization equipment. The waste gas is then treated and discharged.
[0058] S5. Finished product processing: The graphitized material is batch-mixed to ensure uniform mixing of different batches. Magnetic separation equipment is used to remove magnetic impurities from the material. The demagnetized material is then packaged and stored.
[0059] Example 5
[0060] A low-cost method for preparing artificial graphite anodes for high-energy-density energy storage batteries, comprising the following steps:
[0061] S1. Prepare asphalt needle coke material and use a crusher to initially crush large pieces of raw coke to reduce particle size;
[0062] S2. Dry the raw coke by removing moisture through heat conduction, grind the raw coke into powder using a grinding mill, optimize and adjust the shape of the particles using a shaping device to improve the sphericity of the particles, and granulate using a horizontal reactor.
[0063] S3. Calcination: The processed raw coke is fed into the calcination equipment. Based on microwave-assisted calcination, the physical and chemical properties are changed, and the temperature distribution is intelligently controlled during the calcination process.
[0064] S4. Graphitization, based on magnetic field-assisted technology, involves applying a magnetic field at high temperature to transform the crystal structure of the material. Dust and impurities adhering to the surface of the material are removed by cooling and dust removal equipment, and sulfur is removed from the material by desulfurization equipment. The waste gas is then treated and discharged.
[0065] S5. Finished product processing: The graphitized material is batch-mixed to ensure uniform mixing of different batches. Magnetic separation equipment is used to remove magnetic impurities from the material. The demagnetized material is then packaged and stored.
[0066] Table 1 below shows the properties resulting from different ratios of coal-derived needle coke to pitch needle coke in different embodiments:
[0067]
[0068]
[0069] Table 1
[0070] The tap density test procedure is as follows:
[0071] The prepared sample was placed in the graduated cylinder of the tapped density meter. The instrument was set to a vibration frequency of 300 times / minute, an amplitude of 3 mm, and a vibration time of 120 seconds. During the vibration, the sample gradually compacted under the action of gravity and vibration force. After the vibration was completed, the volume of the sample in the graduated cylinder was read, and the mass of the sample was weighed using a high-precision balance. The tapped density was calculated according to the formula ρ = m / V (ρ is the tapped density, m is the mass of the sample, and V is the volume of the sample). The measurement was repeated 3 times and the average value was taken to reduce experimental error.
[0072] Specific surface area test procedure
[0073] The nitrogen adsorption method (BET method) was used. Approximately 0.2-0.5g of sample was placed in a sample tube and degassed in a vacuum environment at 150℃ for 2-4 hours to remove impurity gases adsorbed on the sample surface. The degassed sample tube was then installed on a specific surface area analyzer, and high-purity nitrogen was introduced. Adsorption-desorption experiments were conducted at liquid nitrogen temperature (-196℃). The instrument automatically recorded the amount of nitrogen adsorbed under different pressures. The specific surface area of the sample was calculated using the BET equation. Each sample was tested twice to ensure data accuracy.
[0074] Table 1 above shows that the ratio of coal-based needle coke to pitch needle coke in Example 3 is optimal; the initial discharge capacity is 348-352 mAh / g, the compaction is ≥1.60 g / cm3, and it can stably cycle for more than 3000 cycles at 45℃.
[0075] The raw material selected is coal-based needle coke. Compared with pitch coke, coal-based needle coke removes quinoline insolubles (QI) and metallic impurities during the production stage, making it easier to form a fibrous structure and graphitize during coking. Pitch needle coke particles are also mixed in. The compaction density of pitch coke particles is usually between (1.60-1.70) g·cm-3, while that of pitch needle coke is between (1.70-1.80) g·cm-3, which can achieve a higher compaction density.
[0076] Using a horizontal reactor for granulation reduces the amount of asphalt added and decreases the loss of volume. For the same granulation particle size, 50% less asphalt needs to be added when using a horizontal reactor compared to a smaller particle size.
[0077] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A low-cost method for preparing an artificial graphite anode for a high-energy-density energy storage battery, characterized in that, The preparation steps are as follows: S1. Prepare raw coke materials, including coal-based needle coke and pitch needle coke. Use a crusher to initially crush large pieces of raw coke to reduce particle size. Mix and blend the coal-based needle coke and pitch needle coke. S2. The mixed raw coke is dried by heat conduction to remove moisture. The raw coke is then ground into powder using a grinding mill. The shape of the particles is optimized and adjusted using a shaping device to improve the sphericity of the particles. Granulation is then performed using a horizontal reactor. S3. Calcination: The processed raw coke is fed into the calcination equipment. Based on microwave-assisted calcination, the physical and chemical properties are changed, and the temperature distribution is intelligently controlled during the calcination process. S4. Graphitization, based on magnetic field-assisted technology, involves applying a magnetic field at high temperature to transform the crystal structure of the material. Dust and impurities adhering to the surface of the material are removed by cooling and dust removal equipment, and sulfur is removed from the material by desulfurization equipment. The waste gas is then treated and discharged. S5. Finished product processing: The graphitized material is batch-mixed to ensure uniform mixing of different batches. Magnetic separation equipment is used to remove magnetic impurities from the material. The demagnetized material is then packaged and stored.
2. The low-cost preparation method of artificial graphite anode for high-energy-density energy storage batteries according to claim 1, characterized in that, In step S1, the ratio of coal-series needle coke to pitch needle coke is 10:0, 7:3, 5:5, 3:7 and 0:
10. In the coke crushing stage, a dual-rotor impact crusher is used for two-stage crushing. After being impacted and crushed on the high-speed rotating first-stage rotor, the particles are thrown against the impact plate for further collision and crushing. After fine crushing by the second-stage rotor, the particle size is reduced.
3. The low-cost preparation method of artificial graphite anode for high-energy-density energy storage batteries according to claim 1, characterized in that, In step S2, a vacuum rake dryer is used for drying. The vacuum level is controlled between -0.08MPa and -0.095MPa during operation. The heating temperature of the jacket and hollow shaft is 120-150℃, and heat is transferred through heat conduction. The speed of the rake agitator is 10-15r / min, and the drying time is 2-4h. Drying is stopped when the moisture content of the material drops to 0.5%-1%.
4. The low-cost preparation method of artificial graphite anode for high-energy-density energy storage batteries according to claim 1, characterized in that, In step S2, the feed rate of the grinding mill is 80-120 kg / h, the compressed air pressure is 0.6-0.8 MPa, and the airflow rate is 30-50 m³ / h. 3 The speed is increased to provide sufficient kinetic energy for the material to collide and crush within the grinding chamber, resulting in a finished powder particle size of 10-50μm.
5. A low-cost preparation method for a high-energy-density energy storage battery artificial graphite anode according to claim 1, characterized in that, In step S2, granulation is carried out in a horizontal reactor with a rotation speed of 5-10 r / min, a spray pressure of 0.3-0.5 MPa from the atomizing nozzle, an inlet hot air temperature of 200-250℃ and an outlet temperature of 80-110℃ for drying and granulation. A sieving structure is also provided to separate unqualified particles for regranulation.
6. A low-cost preparation method for a high-energy-density energy storage battery artificial graphite anode according to claim 1, characterized in that, The intelligent temperature distribution control step in step S3 is as follows: Multiple temperature sensors are installed inside the roasting equipment to obtain the surface temperature of the raw coke; temperature data is acquired every 10-20 seconds. The collected data is uploaded to the control system in real time via Ethernet. Based on machine learning algorithms, historical and current data are analyzed to establish a temperature distribution model, predict the temperature change trend under different microwave powers and roasting times, identify local temperature anomalies caused by differences in density and moisture content of raw coke, and generate temperature deviation warnings. Based on the temperature distribution model and preset process parameters, the required microwave power adjustment value for each region is calculated. When the local temperature is detected to be too high, the power of the corresponding microwave generator in that region is automatically reduced; when the temperature in a region is insufficient, the microwave output is increased.
7. A low-cost preparation method for a high-energy-density energy storage battery artificial graphite anode according to claim 1, characterized in that, In step S4, magnetic field-assisted technology is introduced into the graphitization process. A superconducting magnet system is set up around the high-temperature equipment to create a strong magnetic field environment. The superconducting magnet is made of niobium-titanium superconducting material. After the material enters the graphitization furnace, the magnetic field parameters are adjusted to rotate at a speed of 0.5-2 r / s, and the magnetic field strength is dynamically adjusted within the range of 3-10T.
8. A low-cost preparation method for a high-energy-density energy storage battery artificial graphite anode according to claim 7, characterized in that, The superconducting magnet system is equipped with a monitoring device that uses an X-ray diffractometer to detect changes in the crystal structure of the material online. A crystal structure analysis spectrum is generated every 10-15 minutes. The detection data is compared with a preset crystal structure model, and the magnetic field strength, direction, and high-temperature process parameters are adjusted when differences are found.
9. A low-cost preparation method for a high-energy-density energy storage battery artificial graphite anode according to claim 1, characterized in that, The steps in step S4 for removing sulfur from the material by the desulfurization unit are as follows: Physical adsorption pretreatment is adopted. In a packed fixed-bed adsorption tower, modified activated carbon adsorbent is used to capture free sulfur and small molecule sulfur-containing compounds. The adsorbent is regenerated by hot nitrogen purging. The sulfur compounds are converted into hydrogen sulfide for deep desulfurization in the biological desulfurization reactor. During waste gas treatment, the gas passes through an alkaline scrubbing absorption tower where it reacts with acidic sulfur-containing gases, and the alkaline solution is regenerated and recycled. Then, it enters a biological filter where microorganisms degrade organic sulfur. After deep purification by activated carbon adsorption tower, the waste is discharged at high altitude after meeting the standards.
10. A low-cost preparation method for a high-energy-density energy storage battery artificial graphite anode according to claim 1, characterized in that, In step S5, materials from different batches are mixed evenly using a planetary mixer.
Citation Information
Patent Citations
Preparation method of high-compaction artificial graphite negative electrode material
CN107507979A
In-site measuring device for carbon fiber graphitized X-ray scattering for synchrotron radiation
CN109709119A
Coal-based graphite composite material as well as preparation method and application thereof
CN114920243A
Variable frequency microwave heating control method and system of vacuum furnace
CN119879557A